Multiple Incentive Fee Maximization: An Economic Model - Weiner, Neil S. (Quarterly Journal of Economics, 1963)
Introduction, 604. — I. Hypothetical contract of the cost-plus-incentive-fee type, 604. — II. The maximization model, 606. — III. Consideration of the firms entire operations, 612. — IV. Long-run profitability, 614. — V. Conclusion, 615.